(untitled) (Research, Society and Development, 2024)
Portosystemic shunt (PSS) or portosystemic diversion (PSD) is the most common hepatic circulatory anomaly in dogs. This condition results from an abnormal connection between the portal and systemic circulations, diverting blood flow from the liver to varying degrees. These shunts can be extrahepatic (EPSS), located outside the hepatic parenchyma, or intrahepatic (IPSS), within the hepatic parenchyma. Computed tomography (CT) is considered the gold standard diagnostic tool for detecting PSS. Clinical signs of congenital extrahepatic PSS include symptoms related to the central nervous, gastrointestinal, and urinary systems. The only definitive treatment for PSS is surgical intervention or interventional occlusion of the anomalous vessel.A female canine of mixed breed, presenting with low body weight and brittle coat, was attended to at a private clinic in Brasília-DF. Serial examinations and abdominal CT scans were performed, suggesting a possible shunt between the left gastric vein and the portal and caudal vena cava veins. The animal underwent surgery to correct three shunts using the cellophane banding technique. This report aims to describe a case of surgical correction of congenital multiple extrahepatic portosystemic shunts in a female mixed-breed dog using cellophane banding. The methodology employed was a descriptive observational study, in the form of a case report.The findings of this article suggest that the definitive correction of this anomaly is surgical, with cellophane banding being a promising approach in the treatment of dogs affected by PSS.